Enhancing Brake System Evaluation in Periodic Testing of Goods Transport Vehicles through FTA-FMEA Risk Analysis - Irfan Ansori; Dwitya Harits Waskito; Mutharuddin Mutharuddin; Novi Irawati; Sinung Nugroho; Tetty Sulastri Mardiana; Subaryata Subaryata; Nurul Aldha Mauliddina Siregar (Automotive Experiences, 2023)
Failure of the braking system is one of the factors causing traffic accidents, therefore periodic testing of goods transport vehicles is very important. In fact, the incidence rate is still very high despite routine testing. Standard Operating Procedures (SOP) for periodic testing must be updated to reduce the risk of possible accidents. Therefore, procedures for updating the SOP for periodic brake system testing are presented in this article. The Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) methods were applied based on accident investigation data from the National Transportation Safety Committee (NTSC) from 2017 to 2022. FTA is used for risk identification, while FMEA is used for risk analysis to find the highest-risk failure cases. The results of our analysis showed that 13 failure cases were classified as intolerable so additional SOPs were required for each case. Finally, the results of this study provide new insights for stakeholders to revise the rules regarding periodic vehicle testing.